2010
DOI: 10.1088/0960-1317/20/5/055005
|View full text |Cite
|
Sign up to set email alerts
|

Investigating ESD sensitivity in electrostatic SiGe MEMS

Abstract: The sensitivity of electrostatically actuated SiGe microelectromechanical systems to electrostatic discharge events has been investigated in this paper. Torsional micromirrors and RF microelectromechanical systems (MEMS) actuators have been used as two case studies to perform this study. On-wafer electrostatic discharge (ESD) measurement methods, such as the human body model (HBM) and machine model (MM), are discussed. The impact of HBM ESD zap tests on the functionality and behavior of MEMS is explained and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 11 publications
1
4
0
Order By: Relevance
“…As the amplitude of the beam) is increased, the electrostatic force bet and pulls the beam down. As expected, scan points 2 and 3, which are towards the centre of the beam show a higher displacement than points 1 and 4 which are closer to the clamping points [6]. Moreover, the displacement is symmetric with respect to the voltage polarity and is very repeatable for large number of actuation cycles which point towards a well From these results it can be concluded that the not harm the functionality of these MEMS devices.…”
Section: Mems Characterizationsupporting
confidence: 75%
“…As the amplitude of the beam) is increased, the electrostatic force bet and pulls the beam down. As expected, scan points 2 and 3, which are towards the centre of the beam show a higher displacement than points 1 and 4 which are closer to the clamping points [6]. Moreover, the displacement is symmetric with respect to the voltage polarity and is very repeatable for large number of actuation cycles which point towards a well From these results it can be concluded that the not harm the functionality of these MEMS devices.…”
Section: Mems Characterizationsupporting
confidence: 75%
“…Other models like the Machine Model (MM) are also used to model events where machine parts act as the discharge source. Due to the usually large resistance of electrostatic MEMS, the results of tests with the MM and the HBM are very similar 1 .…”
Section: Transient Behaviour Of Mems Tunable Gratings During Esd Eventsmentioning
confidence: 95%
“…Reliability estimation of MEMS devices has been mainly done thorough extensive Electrostatic discharge (ESD) tests 1,2 , shock and vibration tests 3,4 , fatigue and creep tests 5,6 , and aging tests through rapid thermal cycling. These tests have so far mainly been used to qualify devices.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We attributed this malfunction to some repeated impact of electrostatic discharge on the MEMS conductive elements. 21 The MEMS scanning mirror was replaced by the manufacturer and the system was calibrated to its original scan rate and range. To be included in the study, four through twelve-year-old children had to have at least one primary tooth restored with a resin composite.…”
Section: Human Subjectsmentioning
confidence: 99%